The Correlation of Calistung Ability With Readiness Elementary School TK B Children In Seluma District Seluma Regency City - Ayu Lestari, Ditha (CV Media Inti Teknologi, 2024)
Finding out how calistung abilities relate to kids' preparedness for kindergarten B primary school in Seluma Kota District, Seluma Regency, was the aim of this study. This study used a correlational quantitative approach. The population amounted to 168 people and the sample taken amounted to 42 children with sampling techniques using proportional cluster sampling. A questionnaire served as the method of data collecting. Product moment correlation is the analytical method used to analyze research data. The average value in the low group was 2.516, according to the data. There is a strong correlation between preparation for entry into primary school and calistung abilities. This is based on the Pearson product moment significance test which is obtained from a significance value of less than 0.05 (0.306 < 0.05) so that Ha is accepted. It is suggested to future researchers to use different factors such as parents' perceptions of literacy skills.